EUV sources for lithography - Bakshi, Vivek (SPIE, 2006)
This comprehensive volume, edited by a senior technical staff member at SEMATECH, is the authoritative reference book on EUV source technology. The volume contains 38 chapters contributed by leading researchers and suppliers in the EUV source field. Topics range from a state-of-the-art overview and in-depth explanation of EUV source requirements, to fundamental atomic data and theoretical models of EUV sources based on discharge-produced plasmas (DPPs) and laser-produced plasmas (LPPs), to a description of prominent DPP and LPP designs and other technologies for producing EUV radiation. Additional topics include EUV source metrology and components (collectors, electrodes), debris mitigation, and mechanisms of component erosion in EUV sources. The volume is intended to meet the needs of both practitioners of the technology and readers seeking an introduction to the subject.
Keywords: Ultraviolet radiation -- Industrial applications.; Extreme ultraviolet lithography.; Plasma (Ionized gases); Lithography.; elektronické knihy; electronic books